Aspect angle sensitivity of pump-induced optical emissions at EISCAT - Kosch, Michael J.; Bryers, Carl; Rietveld, Michael T; Yeoman, Timothy K; Ogawa, Yasunobu (Earth, Planets and Space, 2014)
Source at https://doi.org/10.1186/s40623-014-0159-x . We investigate the aspect angle sensitivity of the pump-induced artificial optical emissions in the ionosphere over the European Incoherent Scatter Scientific Association (EISCAT) high-frequency transmitter facility at Ramfjord, Norway, as a function of the pump beam launch angle relative to the magnetic field line direction. The highest intensity optical emissions occur when the pump beam pointing direction is in the magnetic zenith (approximately 12° S of local zenith). For pump beam directions further north from field aligned, the optical emission intensity decreases for the same pump power. In addition, the primary photon-emitting region becomes displaced towards the magnetic zenith relative to the pump beam and for larger aspect angles, the brightest emissions were found to be outside the −3-dB pump beam width. The Cooperative UK Twin-Located Auroral Sounding System (CUTLASS) coherent scatter high-frequency (HF) radar detected a quasi-constant level of backscatter power from the pumped ionosphere, indicating that saturated striations were formed for all pump beam directions. This indicates that the presence of upper-hybrid resonance is not sufficient to explain the angular sensitivity of the optical emissions.